UiTM bronchoscopy bootcamp: rapid skills advancement in one day - Samsuddin, Syahrinnaquiah; Alias, Am Basheeri; Yen Shen, Wong; Musa, Aisya Natasya (Faculty of Medicine, 2025)
The Respiratory Unit, Faculty of Medicine UiTM, successfully organized a bronchoscopy bootcamp under the framework of the Persatuan Pendidikan Kesihatan Paru-Paru (PPKP) on 11 October 2025 at UiTM Sungai Buloh. The full-day event, endorsed by the Malaysian Thoracic Society (MTS), attracted participants from multiple healthcare disciplines, including anaesthesiology, acute internal medicine, and general medicine.